ANALYSIS OF KNOWLEDGE AND MOTIVATION OF SEBAYA COUNSELERS IN THE IMPLEMENTATION OF ADOLESCENT REPRODUCTIVE HEALTH COUNSELING IN SUMENEP DISTRICT - Permatasari, Dian (Journal of Vocational Nursing, 2020)
Introduction: The globalization of information has a big impact on adolescents. The great curiosity of adolescents about reproduction encourages adolescents to seek information from various sources, including peers, parents, schools and information media. This requires correct and responsible information so that adolescents can have healthy reproductive behavior. The aim is to analyze the knowledge and motivation of peer counselors in the implementation of adolescent reproductive health counseling in Sumenep Regency. Methods: This study used quantitative methods with cross sectional design. The population in this study is the total population, namely all peer counselors who have received training on Adolescent Reproductive Health in Sumenep Regency as many as 66 people. Sampling technique using simple random sampling. Data analysis used chi-square statistical test and logistic regression. Results: The results showed that knowledge about adolescent reproductive health counseling, motivation towards the implementation of adolescent reproductive health counseling, had an influence on the implementation of adolescent reproductive health counseling. Conclusion: This study recommends the Sumenep Regency BPMP & KB Office to organize and activate adolescent reproductive health counseling training and invite peer counselors who are active in Sumenep district, as well as facilitate any adolescent reproductive health counseling activities in the form of facilities and infrastructure